KOPERASI PASAR SEBAGAI SARANA MEMINIMALISIR “CANDU” TERHADAP BANK TITHIL - Dwi Yanuarindah Putri; Fidyah Jayatri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
loan shark services being commonly seen in traditional markets. The offer of loan shark financial services in the form of easy loans has made many traders easily tempted to take express loans without thinking about the impact. This impact starts from high loan interest, which causes the borrower to have difficulty repaying loan funds. The purpose of this study is to find out more about the formation of cooperatives and the strategy of managing market cooperatives in reducing dependence on traders in traditional markets using loan shark services. The research approach uses qualitative narrative by describing the history of the formation of market cooperatives to the cooperative manager's strategy in attracting traders who for years have used loan shark services to cover all funding needs. The results showed that the formation of a market cooperative was due to the demands of the Probolinggo district government where every market was required to have a cooperative. With courage, honesty and strong determination, cooperative managers believe they can develop cooperatives to eliminate moneylender transactions among traders. Meanwhile, the strategy used is in the form of a familial approach with trust capital among the Bayeman Market traders who are members of the market association organization. Research suggestions for the Probolinggo Regency government through the information on the results of this study can provide real support for policies to develop market cooperatives such as those that have been formed according to the initial commitment.Keywords: : market cooperatives; minimize bank tithil